La experiencia de aprendizaje y su incidencia en el desarrollo de destrezas en niños y niñas de 3 años de edad - Carvajal Cuji, Angélica Carolina (2015)
The purpose of this research project is the implementation of the ethodology of learning experiences for the proper development of skills children three years of age. The teachers of Basic Education Private School # 59''Casiodoro of Reina'' use traditional methods, leading each of the activities and imposing rote learning. Learning experiences are important because they promote bio-psycho-social development of students through totally innovative activities, through which they can create meaningful situations, imagine, experience, socialize with others, ask questions and hypotheses, solve problems, investigate and use its own language, while the work of teachers will guide and implement enriched environments….